Using a complex adaptive system lens to understand family caregiving experiences navigating the stroke rehabilitation system - Ghazzawi, Andrea; Kuziemsky, Craig; O’Sullivan, Tracey (Université d'Ottawa | University of Ottawa, 2016)
Abstract Background Family caregivers provide the stroke survivor with social support and continuity during the transition home from a rehabilitation facility. In this exploratory study we examined family caregivers’ perceptions and experiences navigating the stroke rehabilitation system. The theories of continuity of care and complex adaptive systems were integrated to examine the transition from a stroke rehabilitation facility to the patient’s home. This study provides an understanding of the interacting complexities at the macro and micro levels. Methods A convenient sample of family caregivers (n = 14) who provide care for a stroke survivor were recruited 4–12 weeks following the patient’s discharge from a stroke rehabilitation facility in Ontario, Canada. Interviews were conducted with family caregivers to examine their perceptions and experiences navigating the stroke rehabilitation system. Directed and inductive content analysis and the theory of Complex Adaptive Systems were used to interpret the perceptions of family caregivers. Results Health system policies and procedures at the macro-level determined the types and timing of information being provided to caregivers, and impacted continuity of care and access to supports and services at the micro-level. Supports and services in the community, such as outpatient physiotherapy services, were limited or did not meet the specific needs of the stroke survivors or family caregivers. Conclusion Relationships with health providers, informational support, and continuity in case management all influence the family caregiving experience and ultimately the quality of care for the stroke survivor, during the transition home from a rehabilitation facility.